FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA USAHA PELAYANAN JASA ALSINTAN (UPJA) MENUJU PERTANIAN MODERN DI KABUPATEN SUKOHARJO - Rika Indra Sukmana; Suminah Suminah; Hanifah Ihsaniyati (AGRITEXTS: Journal of Agricultural Extension, 2017)
This research aimed  to know some factors which influenced the performance of Management Unit Service Privider For Agricultural Machineries in Dalangan Village, Tawangsari district, Sukoharjo Regency based on the motivation, management, ability, skills and facilityof UPJA. The basic method used in this research was eksplanative through survey technique.The location of research was done purposively in Sukoharjo regency, Dalangan district considering that this village had wide area of UUPJA (170 Ha) and it had become the national model area. Stratiefed random sampling was used as sampling method in this research, where the strata is based on the board and members, for the selected member of 55 respondents while the board was taken all a number of 15. Total samples were 70 farmers of respondents. The data was gotten by using questionnaire to 70 respondents passed observation, interview, and documentation. The data analysis used in this research was multiple liniear regression with spss 22.00. Then, the result showed that same factors influenced the work performance were motivation was high category, managemen was high categoryt, ability and skills was high category and facilities was high category and the work performance UPJA was high category. There was significant influence among those factors (motivation, management, ability, and skill) with confidence level 95%and there was no significant influence between its facilities and the work performance of UPJA.